Electro Pneumatic Control versus Grafcet - Santos, Adriano A (2015)
The classic methodologies of electro-pneumatic control are essentially based on the Cascade method and a methodology supported by Karnaugh Map. If in the first method, the resolution of pneumatic problem is basically performed by dividing the working sequence in groups, in the second method, the approach is made by the minimization of the control logic equations converting the truth table, to the corresponding logical circuit. In this paper we present an alternative form of a PLC programming, using the Cascade and Karnaugh methods, replacing the classic technique supported by the Grafcet modelling.